KUAT TEKAN DAN TARIK BELAH PADA BETON YANG MENGGUNAKAN AGREGAT KASAR LIMBAH PLASTIK - Erniati Bachtiar; Muh Arief Muzakkir; Takwin Takwin; Sri Gusty; Nur Khaerat Nur (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2021)
Plastic represent thousands of materials with different physical, mechanical, and chemical properties. As plastic demand and usage increase, it is undeniable that the amount of plastic waste will increase. Plastic has the features of which cannot rot; it does not decompose naturally; it cannot absorb water or cannot rust. So it will eventually cause problems for the environment. This study aims to determine the compressive strength and tensile strength of concrete mixes that use coarse aggregates of plastic waste as a substitute for natural aggregates / broken rocks. There are three variations of samples made with mutations in the type of plastic used, namely PP (Polypropylene) plastic, PET (Polyethylene Terephthalate) plastic, and PP & PET combination plastic. The specimen is cylindrical, with a size of 10 cm x 20 cm. Compressive strength and tensile strength testing is carried out at 28 days according to SNI standards. The results obtained the compressive strength obtained on each variation of standard concrete samples, PP aggregate concrete, PET aggregate concrete, and PP & PET aggregate concrete, respectively, of 21.64 MPa, 10.61 MPa, 8.48 MPa, and 10.18 MPa. Whereas for the splitting tensile strength of standard concrete, PP aggregate concrete, PET aggregate concrete, and PP & PET aggregate concrete respectively were 2.86 MPa, 1.80 MPa, 1.70 MPa, and 1.80 MPa.